High-temperature-resistant all-solid-state lithium battery as well as preparation method and application thereof
By using lithium indium alloy and double-layer electrolyte structure in all-solid-state lithium batteries, the problem of increasing interface reaction activity at high temperatures is solved, and the battery's high-temperature cycle stability and capacity retention rate are improved.
Patent Information
- Application Number
- CN202411390453.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
Traditional all-solid-state lithium batteries increase the interface reaction activity under high temperature conditions, resulting in a decrease in interface stability and rapid attenuation of battery performance.
The negative electrode layer, electrolyte layer and positive electrode layer structure are arranged in sequence, wherein the negative electrode layer is lithium indium alloy, the electrolyte layer consists of a sulfide layer and a halide layer, and the sulfide layer is located between the halide layer and the negative electrode layer to form a negative electrode. The structure of layer + sulfide layer + halide layer + positive electrode layer enhances the stability of the electrolyte layer.
The cycle stability and battery capacity retention rate of lithium batteries are significantly improved under high temperature conditions, especially when the mass ratio of halide and sulfide is 7:3, the battery's high-temperature capacity retention rate is relatively high.
Smart Images

Figure CN119253036A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and specifically relates to a high temperature resistant all-solid-state lithium battery and a preparation method and application thereof. Background Art
[0002] High temperature resistant all-solid-state lithium batteries have become one of the important choices for the development of a new generation of power batteries due to their high safety and high energy density. The halide solid electrolyte not only has good air stability and high ionic conductivity, but also has a relatively wide electrochemical window, which is compatible with high-voltage positive electrode materials. And thermodynamic analysis shows that the stability of halide solid electrolytes and positive electrode active materials is also significantly better than that of sulfides, which makes them have good stability with positive electrode active materials under high temperature conditions.
[0003] The traditional view is that in a high temperature environment, the electrolyte ion conductivity will increase with the increase of temperature, thus making the electrochemical performance of the battery better. However, in fact, when the temperature is higher than 60°C, the activity of the interface reaction will increase significantly, the interface stability will drop rapidly, and a large number of side reactions will occur at the interface, which will lead to a rapid attenuation of the battery performance. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a high temperature resistant all-solid-state lithium battery and a preparation method and application thereof, wherein the high temperature resistant all-solid-state lithium battery has good cycle stability under high temperature conditions.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a high temperature resistant all-solid-state lithium battery, comprising:
[0007] A negative electrode layer, an electrolyte layer and a positive electrode layer are stacked in sequence;
[0008] The component of the negative electrode layer is lithium-indium alloy;
[0009] The electrolyte layer includes a sulfide layer and a halide layer stacked in sequence;
[0010] The sulfide layer is composed of a sulfide solid electrolyte; the halide layer is composed of a first halide solid electrolyte; the sulfide layer is located between the halide layer and the negative electrode layer, forming a structure of negative electrode layer + sulfide layer + halide layer + positive electrode layer;
[0011] The positive electrode layer includes a positive electrode active material and a second halide solid electrolyte.
[0012] Preferably, the sulfide solid electrolyte is Li 5.4 PS 4.4 Cl1.6 、Li6PS5Cl、Li6PS5Cl 0.5 Br 0.5 , Li 10 GeP2S 12 or Li7P3S 11 .
[0013] Preferably, the first halide solid electrolyte and the second halide solid electrolyte are independently Li3InCl6, Li2ZrCl6, Li3YCl6, Li3YBr3Cl3 or LiAlCl4.
[0014] Preferably, the positive electrode active material is NCM811, NCM83 or NCM9.
[0015] Preferably, the mass ratio of the positive electrode active material to the second halide solid electrolyte in the positive electrode layer is 6-9:4-1.
[0016] Preferably, the mass ratio of the sulfide solid electrolyte in the sulfide layer to the first halide solid electrolyte in the halide layer is 2-8:8-2.
[0017] Preferably, the mass proportion of lithium in the lithium-indium alloy is 3-6%.
[0018] Preferably, it also includes: a negative electrode collector arranged outside the negative electrode layer and a positive electrode collector arranged outside the positive electrode layer; the negative electrode collector is copper foil, stainless steel or foam copper; the positive electrode collector is aluminum foil, stainless steel or graphene.
[0019] The present invention also provides a method for preparing the high temperature resistant all-solid-state lithium battery described in the above technical solution, comprising the following steps:
[0020] Mixing the positive electrode active material and the second halide solid electrolyte to obtain a composite positive electrode powder;
[0021] The sulfide solid electrolyte is first pressed to obtain a sulfide layer;
[0022] Placing a first halide solid electrolyte on one side of the sulfide layer for a second pressing to obtain a sulfide layer + a halide layer;
[0023] Placing the composite positive electrode powder on the side of the sulfide layer + halide layer where the halide layer does not contact the sulfide layer for a third pressing to obtain a sulfide layer + halide layer + positive electrode layer;
[0024] The lithium-indium alloy is placed on the side of the sulfide layer + halide layer + positive electrode layer where the sulfide layer does not contact the halide layer, and a fourth pressing is performed to form a structure of a negative electrode layer + sulfide layer + halide layer + positive electrode layer to obtain the high temperature resistant all-solid-state lithium battery.
[0025] The present invention also provides the use of the high temperature resistant all-solid-state lithium battery described in the above technical solution or the high temperature resistant all-solid-state lithium battery prepared by the preparation method described in the above technical solution in a high temperature environment.
[0026] The present invention provides a high temperature resistant all-solid-state lithium battery, comprising: a negative electrode layer, an electrolyte layer and a positive electrode layer stacked in sequence; the component of the negative electrode layer is a lithium-indium alloy; the electrolyte layer comprises a sulfide layer and a halide layer stacked in sequence; the component of the sulfide layer is a sulfide solid electrolyte; the component of the halide layer is a first halide solid electrolyte; the sulfide layer is located between the halide layer and the negative electrode layer, forming a structure of a negative electrode layer + sulfide layer + halide layer + positive electrode layer; the component of the positive electrode layer comprises a positive electrode active material and a second halide solid electrolyte. The present invention obtains a positive electrode layer by compounding a positive electrode active material and a halide solid electrolyte, the negative electrode layer is a lithium-indium alloy, and the electrolyte layer adopts a double-layer electrolyte structure of a halide layer plus a sulfide layer, and a high temperature resistant all-solid-state lithium battery with good high temperature stability is assembled, the halide solid electrolyte not only has good air stability and high ionic conductivity, but also has the advantages of a wide electrochemical window and good thermal stability, and can be well compatible with the positive electrode active material under high temperature conditions. However, due to the poor stability between the halide solid electrolyte and the lithium-indium alloy, the present invention adds a sulfide layer between the halide layer and the lithium-indium alloy to improve the stability, so that the high-temperature resistant all-solid-state lithium battery can still be stably cycled under high temperature conditions. The results of the embodiment show that the high-temperature resistant all-solid-state lithium battery provided by the present invention has good high-temperature stability when the electrolyte layer uses halides and sulfides in different mass ratios, especially when the mass ratio of halide to sulfide is 7:3, the high-temperature capacity retention rate of the battery is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The SEM, XRD and EIS comparison diagrams of Li3InCl6 (LIC) before and after ball milling in Example 1;
[0028] Figure 2 Long cycle diagram of the high temperature resistant all-solid-state lithium battery assembled in Examples 1 to 3 at 80°C;
[0029] Figure 3 This is a comparison diagram of the impedance of the high temperature resistant all-solid-state lithium battery assembled in Examples 1 to 3 before and after cycling;
[0030] Figure 4 This is the long cycle diagram of the all-solid-state lithium battery assembled in Comparative Examples 1 and 2 at 80°C. DETAILED DESCRIPTION
[0031] The present invention provides a high temperature resistant all-solid-state lithium battery, comprising:
[0032] A negative electrode layer, an electrolyte layer and a positive electrode layer are stacked in sequence;
[0033] The component of the negative electrode layer is lithium-indium alloy;
[0034] The electrolyte layer includes a sulfide layer and a halide layer stacked in sequence;
[0035] The sulfide layer is composed of a sulfide solid electrolyte; the halide layer is composed of a first halide solid electrolyte; the sulfide layer is located between the halide layer and the negative electrode layer, forming a structure of negative electrode layer + sulfide layer + halide layer + positive electrode layer;
[0036] The positive electrode layer includes a positive electrode active material and a second halide solid electrolyte.
[0037] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.
[0038] The high temperature resistant all-solid-state lithium battery provided by the present invention comprises: a negative electrode layer, an electrolyte layer and a positive electrode layer which are stacked in sequence.
[0039] As an embodiment, the negative electrode layer is composed of a lithium-indium alloy.
[0040] As an implementation mode, the mass proportion of lithium in the lithium-indium alloy is 3-6%, and in a specific embodiment, it is 4.5%.
[0041] As an embodiment, the preparation method of the lithium-indium alloy comprises the following steps:
[0042] The lithium foil and the indium foil are stacked in sequence in a mold in the order of indium-lithium-indium-lithium-indium, and pressed to obtain the lithium-indium alloy.
[0043] As an implementation mode, the thickness of the lithium foil is 0.05 mm; the thickness of the indium foil is 0.05 mm; the lithium foil is in the shape of a disc with a diameter of 10 mm; the indium foil is in the shape of a disc with a diameter of 10 mm; the mold is an infrared mold, and the inner diameter of the infrared mold is 10 mm; the pressing pressure is 3.5 t; the pressing time is 10 min; after the pressing is completed, it also includes: taking out the lithium-indium alloy obtained by pressing and removing the edge burrs.
[0044] As an embodiment, the thickness of the negative electrode layer is 0.11 mm.
[0045] As an embodiment, the electrolyte layer includes a sulfide layer and a halide layer stacked in sequence; the component of the sulfide layer is a sulfide solid electrolyte; the component of the halide layer is a first halide solid electrolyte; the sulfide layer is located between the halide layer and the negative electrode layer, forming a structure of negative electrode layer + sulfide layer + halide layer + positive electrode layer.
[0046] As an embodiment, the sulfide solid electrolyte is Li 5.4 PS 4.4 Cl 1.6 、Li6PS5Cl、Li6PS5Cl 0.5 Br 0.5 , Li 10 GeP2S 12 or Li7P3S 11 , in the specific embodiment, Li 5.4 PS 4.4 Cl 1.6 (denoted as LPSC).
[0047] As an embodiment, the first halide solid electrolyte is Li3InCl6, Li2ZrCl6, Li3YCl6, Li3YBr3Cl3 or LiAlCl4, and in a specific embodiment it is Li3InCl6 (denoted as LIC).
[0048] As an implementation mode, the mass ratio of the sulfide solid electrolyte in the sulfide layer to the first halide solid electrolyte in the halide layer is 2-8:8-2, and in a specific embodiment is 3-7:7-3.
[0049] As an embodiment, the thickness of the electrolyte layer is 0.58-0.71 mm, and in a specific embodiment, it is 0.71 mm; the thickness of the sulfide layer is 0.25 mm-0.57 mm, and in a specific embodiment, it is 0.57 mm; the thickness of the halide layer is 0.14 mm-0.33 mm, and in a specific embodiment, it is 0.14 mm.
[0050] As an embodiment, the positive electrode layer comprises a positive electrode active material and a second halide solid electrolyte.
[0051] As an embodiment, the positive electrode active material is NCM811, NCM83 or NCM9, and in a specific embodiment, it is NCM9. The positive electrode active materials are all purchased from CLUDE.
[0052] As an embodiment, the second halide solid electrolyte is Li3InCl6, Li2ZrCl6, Li3YCl6, Li3YBr3Cl3 or LiAlCl4, and in a specific embodiment it is Li3InCl6 (denoted as LIC).
[0053] As an implementation manner, the mass ratio of the positive electrode active material to the second halide solid electrolyte in the positive electrode layer is 6-9:4-1, and in a specific embodiment is 7:3.
[0054] As an embodiment, the loading amount of the positive electrode active material in the positive electrode layer of the high temperature resistant all-solid-state lithium battery is 10 to 15 mg cm -2 , as another embodiment, 13 to 14 mg·cm -2 .
[0055] As an embodiment, the thickness of the positive electrode layer is 0.06 mm.
[0056] As an embodiment, the high temperature resistant all-solid-state lithium battery further includes: a negative electrode current collector disposed outside the negative electrode layer and a positive electrode current collector disposed outside the positive electrode layer.
[0057] As an implementation manner, the negative electrode current collector is copper foil, stainless steel or foam copper, and in a specific embodiment, it is copper foil.
[0058] As an implementation mode, the positive electrode current collector is aluminum foil, stainless steel or graphene, and in a specific embodiment, it is aluminum foil.
[0059] As an embodiment, the high temperature resistant all-solid-state lithium battery further includes: a stainless steel shell arranged on the outermost layer.
[0060] As an embodiment, the high temperature resistant all-solid-state lithium battery has a discharge capacity of >120 mAh·g after 100 cycles at 80°C. -1 , capacity retention rate>65%.
[0061] As another embodiment, the high temperature resistant all-solid-state lithium battery has a discharge capacity of 124.30 to 141.95 mAh·g after 100 cycles at 80°C. -1 , the capacity retention rate is 65.4~83.94%.
[0062] The present invention obtains a positive electrode layer by compounding a positive electrode active material and a halide solid electrolyte, a negative electrode layer is a lithium-indium alloy, and an electrolyte layer adopts a double-layer electrolyte structure of a halide layer plus a sulfide layer, and assembles a high-temperature resistant all-solid-state lithium battery with good high-temperature stability. The halide solid electrolyte not only has good air stability and high ion conductivity, but also has the advantages of a wide electrochemical window and good thermal stability, and can be well compatible with the positive electrode active material under high temperature conditions. However, due to the poor stability between the halide solid electrolyte and the lithium-indium alloy, the present invention adds a sulfide layer between the halide layer and the lithium-indium alloy to improve the stability, so that the high-temperature resistant all-solid-state lithium battery can still be stably cycled under high temperature conditions.
[0063] The present invention also provides a method for preparing the high temperature resistant all-solid-state lithium battery described in the above technical solution, comprising the following steps:
[0064] Mixing the positive electrode active material and the second halide solid electrolyte to obtain a composite positive electrode powder;
[0065] The sulfide solid electrolyte is first pressed to obtain a sulfide layer;
[0066] Placing a first halide solid electrolyte on one side of the sulfide layer for a second pressing to obtain a sulfide layer + a halide layer;
[0067] Placing the composite positive electrode powder on the side of the sulfide layer + halide layer where the halide layer does not contact the sulfide layer for a third pressing to obtain a sulfide layer + halide layer + positive electrode layer;
[0068] The lithium-indium alloy is placed on the side of the sulfide layer + halide layer + positive electrode layer where the sulfide layer does not contact the halide layer, and a fourth pressing is performed to form a structure of a negative electrode layer + sulfide layer + halide layer + positive electrode layer to obtain the high temperature resistant all-solid-state lithium battery.
[0069] The present invention mixes the positive electrode active material and the second halide solid electrolyte to obtain composite positive electrode powder.
[0070] As an embodiment, before mixing the positive electrode active material and the second halide solid electrolyte, the present invention places the second halide solid electrolyte and ball milling beads in a ball milling jar, and then transfers the ball milling jar to a planetary ball mill for ball milling. Then, the ball milling jar is transferred to a glove box to scrape off the powder adhering to the inner wall of the ball milling jar, and then ball milling is performed again. This process is repeated 3 to 4 times.
[0071] As an embodiment, the particle size of the second halide solid electrolyte is 5 to 20 μm; the ball milling beads are zirconia ball milling beads; the mass ratio of the second halide solid electrolyte to the ball milling beads is 1:20; the ball milling speed is 400 rpm; and the ball milling time is 1 hour.
[0072] In the present invention, the particles of the halide solid electrolyte are relatively large, with a particle size of 5 to 20 μm. If they are directly compounded with the positive electrode active material, the contact effect will be extremely poor, so the halide solid electrolyte particles are crushed by ball milling. The crystal structure of the halide solid electrolyte after ball milling is severely damaged, and the ion conductivity is greatly reduced. Therefore, only the halide solid electrolyte with a small particle size after ball milling is used for the preparation of the composite positive electrode, and the electrolyte layer uses the halide solid electrolyte with high conductivity that has not been ball milled.
[0073] As an implementation mode, the positive electrode active material and the second halide solid electrolyte are mixed under grinding conditions; the grinding is manual grinding; and the grinding time is 30 minutes.
[0074] The present invention performs a first pressing on the sulfide solid electrolyte to obtain a sulfide layer.
[0075] As an implementation mode, the first pressing is performed in an infrared mold; the equipment used for the first pressing is a press; the pressure of the first pressing is 0.5t, and the holding time is 10s.
[0076] After obtaining the sulfide layer, the present invention places the first halide solid electrolyte on one side of the sulfide layer for a second pressing to obtain a sulfide layer + a halide layer.
[0077] As an implementation mode, the second pressing is performed in an infrared mold; the equipment used for the second pressing is a press; the pressure of the second pressing is 2t, and the holding time is 10s.
[0078] After obtaining the sulfide layer + halide layer, the present invention places the composite positive electrode powder on the side of the sulfide layer + halide layer where the halide layer does not contact the sulfide layer for a third pressing to obtain the sulfide layer + halide layer + positive electrode layer.
[0079] As an implementation mode, the third pressing is performed in an infrared mold; the equipment used for the third pressing is a press; the pressure of the third pressing is 4t, and the holding time is 5min.
[0080] After obtaining the sulfide layer + halide layer + positive electrode layer, the present invention places a lithium indium alloy on the side of the sulfide layer + halide layer + positive electrode layer where the sulfide layer does not contact the halide layer, and performs a fourth pressing to form a structure of a negative electrode layer + sulfide layer + halide layer + positive electrode layer to obtain the high temperature resistant all-solid-state lithium battery.
[0081] As an implementation mode, the fourth pressing is performed in a polyetheretherketone (PEEK) mold; the equipment used for the fourth pressing is a press; the pressure of the fourth pressing is 4t, and the holding time is 5min.
[0082] As an embodiment, when the high temperature resistant all-solid-state lithium battery further includes: a negative electrode current collector arranged on the outside of the negative electrode layer and a positive electrode current collector arranged on the outside of the positive electrode layer, the present invention places the positive electrode current collector on the outside of the positive electrode layer in the sulfide layer + halide layer + positive electrode layer, and places the lithium indium alloy and the negative electrode current collector in sequence on the outside of the sulfide layer in the sulfide layer + halide layer + positive electrode layer, and performs a fourth pressing to obtain the high temperature resistant all-solid-state lithium battery.
[0083] As an embodiment, when the high temperature resistant all-solid-state lithium battery also includes a stainless steel shell arranged on the outermost layer, the present invention encapsulates the high temperature resistant all-solid-state lithium battery obtained by the fourth pressing in the stainless steel shell and then presses it to obtain a high temperature resistant all-solid-state lithium battery product.
[0084] The present invention provides the use of the high temperature resistant all-solid-state lithium battery described in the above technical solution or the high temperature resistant all-solid-state lithium battery prepared by the preparation method described in the above technical solution in a high temperature environment.
[0085] The present invention has no special limitation on the application of the high temperature resistant all-solid-state lithium battery in a high temperature environment, and any application method known in the art may be used.
[0086] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.
[0087] Example 1
[0088] Preparation of small-particle Li3InCl6 (LIC): Weigh 4 g of commercial LIC and 80 g of zirconium oxide ball milling beads and place them in a ball milling jar, seal them, transfer the ball milling jar to a planetary ball mill, and mill them at 400 rpm for 1 h. Then transfer the ball milling jar to a glove box to scrape off the powder adhering to the inner wall of the jar, and then mill again. Repeat this process 3 times to obtain refined LIC.
[0089] Preparation of composite cathode powder: 2.8 g NCM9 and 1.2 g refined LIC were weighed and placed in a mortar and ground manually with a pestle for 30 min to obtain a composite cathode powder of NCM9+LIC;
[0090] Preparation of lithium-indium alloy: Lithium foil and indium foil with a thickness of 0.05 mm were cut into discs with a diameter of 10 mm, and stacked in the order of indium-lithium-indium-lithium-indium in an infrared mold with an inner diameter of 10 mm. The alloying was performed under a pressure of 3.5 tons for 10 minutes, and the edge burrs were removed after being taken out to obtain a lithium-indium alloy with a lithium mass ratio of 4.5%;
[0091] Assembly of LiIn|LPSC|LIC|NCM9+LIC (refined) high temperature resistant all-solid-state lithium battery: first weigh 70 mg of LPSC electrolyte, add it to the infrared mold and flatten it with a pressure rod, keep the pressure at 0.5t for 10s under a press to obtain a sulfide layer, then weigh 30 mg of LIC electrolyte, add it to the surface of the sulfide layer, flatten it with a pressure rod, and keep the pressure at 2t for 10s under a press to obtain a sulfide layer + halide layer, finally weigh 15 mg of the above composite positive electrode powder, add it to the surface of the halide layer, flatten it with a pressure rod, and keep the pressure at 4t for 5min under a press to obtain a sulfide layer + halide layer + positive electrode layer; transfer the positive electrode + electrolyte structure obtained by pressing to a polyetheretherketone (PEEK) mold, add aluminum foil to the outside of the positive electrode layer, and press it. Lithium indium alloy and copper foil were added to the outside of the sulfide layer in turn, and then the PEEK mold was placed under a press and maintained at a pressure of 4t for 5 minutes. Finally, the PEEK mold was fixed with a stainless steel shell for subsequent electrochemical testing. The thickness of the negative electrode layer in the obtained high-temperature resistant all-solid-state lithium battery was 0.11mm, the thickness of the electrolyte layer was 0.71mm, the thickness of the sulfide layer was 0.57mm, the thickness of the halide layer was 0.14mm, and the thickness of the positive electrode layer was 0.06mm.
[0092] Example 2
[0093] The difference from Example 1 is that 50 mg of LPSC electrolyte is weighed first, and then 50 mg of LIC electrolyte is weighed, that is, the mass ratio of LIC in the halide layer to LPSC in the sulfide layer is 5:5, and the remaining assembly steps are the same as Example 1.
[0094] Example 3
[0095] The difference from Example 1 is that 30 mg of LPSC electrolyte is weighed first, and then 70 mg of LIC electrolyte is weighed, that is, the mass ratio of LIC in the halide layer to LPSC in the sulfide layer is 7:3, and the remaining assembly steps are the same as Example 1.
[0096] Comparative Example 1
[0097] Preparation of small-particle LPSC: Like LIC in the example, commercial LPSC particles are relatively large, and direct composite with the positive electrode active material will result in extremely poor contact effect, so the LPSC particles are crushed in the same way. The particle size of the LPSC electrolyte after ball milling is significantly reduced, but the crystal structure is damaged and the ion conductivity is significantly reduced. Therefore, the small-particle LPSC after ball milling is used for the preparation of the composite positive electrode, and the electrolyte layer uses the LPSC with high conductivity that has not been ball milled;
[0098] Preparation of composite cathode: 2.8 g NCM9 and 1.2 g refined LPSC were weighed and placed in a mortar and ground manually with a pestle for 30 min to obtain a composite cathode powder of NCM9+LPSC;
[0099] Preparation of lithium-indium alloy: Lithium foil and indium foil with a thickness of 0.05 mm were cut into discs with a diameter of 10 mm, and stacked in the order of indium-lithium-indium-lithium-indium in an infrared mold with an inner diameter of 10 mm. The alloying was performed under a pressure of 3.5 tons for 10 minutes, and the edge burrs were removed after being taken out to obtain a lithium-indium alloy with a lithium mass ratio of 4.5%;
[0100] Assembly of LiIn|LPSC|NCM9+LPSC (refined) all-solid-state lithium battery: first weigh 70 mg of LPSC electrolyte, add it to the infrared mold and flatten it with a pressure rod, and maintain the pressure at 2t for 10s under a press to obtain a sulfide layer, then weigh 15 mg of composite positive electrode powder, add it to the surface of the sulfide layer, flatten it with a pressure rod, and maintain the pressure at 4t for 5min under a press to obtain a sulfide layer + positive electrode layer, and transfer the pressed positive electrode + electrolyte structure to a polyetheretherketone (PEEK) mold, add aluminum foil to the outside of the positive electrode layer, and add lithium indium alloy and copper foil to the outside of the sulfide layer in turn, then place the PEEK mold under a press and maintain the pressure at 4t for 5min, and finally fix the PEEK mold with a stainless steel shell for subsequent electrochemical testing.
[0101] Comparative Example 2
[0102] Preparation of composite cathode: 2.8 g LiNbO3-coated NCM9 (LNO@NCM9, purchased from CROOD, product number Canrd MA-EN-CA-1H024V) and 1.2 g refined LPSC were weighed and placed in a mortar and manually ground with a pestle for 30 min to obtain a composite cathode powder of LNO@NCM9+LPSC;
[0103] Preparation of lithium-indium alloy: Lithium foil and indium foil with a thickness of 0.05 mm were cut into discs with a diameter of 10 mm, and stacked in the order of indium-lithium-indium-lithium-indium in an infrared mold with an inner diameter of 10 mm. The alloying was performed under a pressure of 3.5 tons for 10 minutes, and the edge burrs were removed after being taken out to obtain a lithium-indium alloy with a lithium mass ratio of 4.5%;
[0104] Assembly of LiIn|LPSC|LNO@NCM9+LPSC (refined) all-solid-state lithium battery: first weigh 70 mg of LPSC electrolyte, add it to the infrared mold and flatten it with a pressure rod, and maintain the pressure at 2t for 10s under the press to obtain a sulfide layer, then weigh 15 mg of composite positive electrode powder, add it to the surface of the sulfide layer, flatten it with a pressure rod, and maintain the pressure at 4t for 5min under the press to obtain a sulfide layer + positive electrode layer, and transfer the pressed positive electrode + electrolyte structure to a polyetheretherketone (PEEK) mold, add aluminum foil to the outside of the positive electrode layer, and add lithium indium alloy and copper foil to the outside of the sulfide layer in turn, then place the PEEK mold under the press and maintain the pressure at 4t for 5min, and finally fix the PEEK mold with a stainless steel shell for subsequent electrochemical testing.
[0105] Performance Testing
[0106] (1) Figure 1 These are the SEM, XRD and EIS comparison diagrams of Li3InCl6 (LIC) before and after ball milling in Example 1, where a is the SEM diagram before ball milling, b is the SEM diagram after ball milling, c is the XRD comparison diagram before and after ball milling, and d is the EIS comparison diagram before and after ball milling.
[0107] from Figure 1 It can be seen that although ball milling effectively reduces the particle size of LIC, it also destroys the crystal structure of LIC to a certain extent, resulting in a significant decrease in ionic conductivity. Therefore, the present invention only uses small-particle LIC after ball milling to mix with NCM9 to prepare a composite positive electrode to improve the contact effect between LIC and the positive electrode active material, while the electrolyte layer still uses LIC with higher ionic conductivity that has not been ball milled.
[0108] (2) Electrochemical tests were performed on the high temperature resistant all-solid-state lithium batteries assembled in Examples 1 to 3: The batteries were placed in a high and low temperature oven at 80°C, and the charge and discharge voltage range was set to 2.2 to 3.7 V vs. In / LiIn (i.e., 2.8 to 4.3 V vs. Li / Li + ), first activated at a current density of 0.1C for 3 cycles, and then cycled at a current density of 0.5C for 100 cycles. The results are shown in Figure 2 As shown, Figure 2 LIC:LPSC=3:7 / 5:5 / 7:3 refer to the batteries in Examples 1, 2, and 3, respectively.
[0109] from Figure 2 It can be seen that the high temperature resistant all-solid-state lithium battery assembled in Example 1 has a positive electrode active material loading of 13.46 mg cm -2 The initial discharge capacity at 0.1C is 214.78 mAh g -1The first coulombic efficiency is 83.64%. After 3 cycles of 0.1C activation, the discharge capacity at 0.5C is 190.06mAh·g -1 , the coulombic efficiency is 96.09%. In the subsequent 0.5C cycle, the coulombic efficiency is stable at more than 99%. After 100 cycles at 80℃, the discharge capacity is 124.30mAh·g -1 , the capacity retention rate is 65.40%.
[0110] The high temperature resistant all-solid-state lithium battery assembled in Example 2 has a positive electrode active material loading of 13.46 mg cm -2 The initial discharge capacity at 0.1C is 205.23 mAh g -1 The first coulombic efficiency is 83.96%. After 3 cycles of 0.1C activation, the discharge capacity at 0.5C is 177.89mAh·g -1 , the coulombic efficiency is 95.43%. In the subsequent 0.5C cycle, the coulombic efficiency is basically maintained above 99%. After 100 cycles at 80℃, the discharge capacity is 126.80mAh·g -1 , the capacity retention rate is 71.28%.
[0111] The high temperature resistant all-solid-state lithium battery assembled in Example 3 has a positive electrode active material loading of 13.29 mg cm -2 The initial discharge capacity at 0.1C is 183.97 mAh g -1 The first coulombic efficiency is 87.57%. After 3 cycles of 0.1C activation, the discharge capacity at 0.5C is 169.11 mAh g -1 , the coulombic efficiency is 96.41%, and in the subsequent 0.5C cycle, the coulombic efficiency is stable at more than 99%. After 100 cycles at 80℃, the discharge capacity is 141.95mAh·g -1 , the capacity retention rate is 83.94%.
[0112] (3) The high temperature resistant all-solid-state lithium batteries in Examples 1 to 3 were subjected to impedance analysis before and after high temperature cycling. Figure 3 As shown, a is before the cycle and b is after the cycle.
[0113] from Figure 3It can be seen from a that the highest impedance before cycling is the highest for a high temperature resistant all-solid-state lithium battery with a LIC to LPSC mass ratio of 3:7, and the highest impedance is the highest for a high temperature resistant all-solid-state lithium battery with a LIC to LPSC mass ratio of 7:3. This also corresponds to the highest initial discharge capacity, where the highest discharge capacity is the highest for a high temperature resistant all-solid-state lithium battery with a LIC to LPSC mass ratio of 3:7, and the lowest for a high temperature resistant all-solid-state lithium battery with a LIC to LPSC mass ratio of 7:3. Figure 3 As can be seen from Figure b, the highest impedance after cycling is for the high temperature resistant all-solid-state lithium battery with a LIC to LPSC mass ratio of 3:7, and the lowest impedance is for the high temperature resistant all-solid-state lithium battery with a LIC to LPSC mass ratio of 3:7. This also corresponds to the fact that after cycling 100 times at 80°C, the high temperature resistant all-solid-state lithium battery with a LIC to LPSC mass ratio of 7:3 has the highest discharge specific capacity and capacity retention rate.
[0114] By comparison, the three batteries with different electrolyte ratios all showed good high temperature stability at 80°C. Although the initial discharge capacity of the battery was lower as the proportion of halide in the double-layer electrolyte increased, it showed a higher discharge specific capacity in the subsequent long cycle, and more importantly, the capacity retention rate was greatly improved compared with the previous two.
[0115] (4) The all-solid-state lithium batteries assembled in Comparative Examples 1 and 2 were subjected to electrochemical testing: the batteries were placed in a high and low temperature oven at 80°C, and the charge and discharge voltage range was set to 2.2 to 3.7 V vs. In / LiIn (i.e., 2.8 to 4.3 V vs. Li / Li + ), first activated at a current density of 0.1C for 3 cycles, and then cycled at a current density of 0.5C for 100 cycles. The results are shown in Figure 4 As shown, Figure 4 NCM9+LPSC and LNO@NCM9+LPSC refer to the batteries in Comparative Examples 1 and 2, respectively.
[0116] from Figure 4 It can be seen that the active material loading of the all-solid-state lithium battery assembled in Comparative Example 1 is 13.91 mg cm -2 The initial discharge capacity at 0.1C is 214.70 mAh g -1 The first coulombic efficiency is 90.68%. After 3 cycles of 0.1C activation, the discharge capacity at 0.5C is 169.91mAh·g -1 , the coulombic efficiency is 90.65%. In the subsequent 0.5C cycle, the coulombic efficiency is only maintained above 98%. After 100 cycles at 80℃, the discharge capacity is 27.72mAh·g -1 , the capacity retention rate is 16.31%.
[0117] The all-solid-state lithium battery assembled in Comparative Example 2 has an active material loading of 13.46 mg cm -2 The initial discharge capacity at 0.1C is 217.66 mAh g -1 The first coulombic efficiency is 90.96%. After 3 cycles of 0.1C activation, the discharge capacity at 0.5C is 174.48mAh·g -1 , the coulombic efficiency is 91.26%, and in the subsequent 0.5C cycle, the coulombic efficiency is maintained above 99%. After 100 cycles at 80℃, the discharge capacity is 37.38mAh·g -1 , the capacity retention rate is 21.42%.
[0118] From the above analysis, it can be seen that the high temperature resistant all-solid-state lithium battery with the LiIn|LPSC|LIC|NCM9+LIC structure proposed in the present invention can operate stably at high temperatures, and has greater application value in high temperature environments compared to the traditional LiIn|LPSC|NCM9+LPSC all-solid-state lithium battery.
[0119] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A high temperature resistant all-solid-state lithium battery, characterized in that: include: A negative electrode layer, an electrolyte layer and a positive electrode layer are stacked in sequence; The component of the negative electrode layer is lithium-indium alloy; The electrolyte layer includes a sulfide layer and a halide layer stacked in sequence; The sulfide layer is composed of a sulfide solid electrolyte; the halide layer is composed of a first halide solid electrolyte; the sulfide layer is located between the halide layer and the negative electrode layer, forming a structure of negative electrode layer + sulfide layer + halide layer + positive electrode layer; The positive electrode layer includes a positive electrode active material and a second halide solid electrolyte.
2. The high temperature resistant all-solid-state lithium battery according to claim 1, characterized in that: The sulfide solid electrolyte is Li 5.4 PS 4.4 Cl 1.6 、Li6PS5Cl、Li6PS5Cl 0.5 Br 0.5 , Li 10 GeP2S 12 or Li7P3S 11 .
3. The high temperature resistant all-solid-state lithium battery according to claim 1, characterized in that: The first halide solid electrolyte and the second halide solid electrolyte are independently Li3InCl6, Li2ZrCl6, Li3YCl6, Li3YBr3Cl3 or LiAlCl4.
4. The high temperature resistant all-solid-state lithium battery according to claim 1, characterized in that: The positive electrode active material is NCM811, NCM83 or NCM9.
5. The high temperature resistant all-solid-state lithium battery according to claim 1, 3 or 4, characterized in that: The mass ratio of the positive electrode active material to the second halide solid electrolyte in the positive electrode layer is 6-9:4-1.
6. The high temperature resistant all-solid-state lithium battery according to claim 1, 2 or 3, characterized in that: The mass ratio of the sulfide solid electrolyte in the sulfide layer to the first halide solid electrolyte in the halide layer is 2-8:8-2.
7. The high temperature resistant all-solid-state lithium battery according to claim 1, characterized in that: The mass proportion of lithium in the lithium-indium alloy is 3-6%.
8. The high temperature resistant all-solid-state lithium battery according to claim 1, characterized in that: Also includes: A negative electrode current collector is arranged outside the negative electrode layer and a positive electrode current collector is arranged outside the positive electrode layer; the negative electrode current collector is copper foil, stainless steel or foam copper; the positive electrode current collector is aluminum foil, stainless steel or graphene.
9. The method for preparing a high temperature resistant all-solid-state lithium battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mixing the positive electrode active material and the second halide solid electrolyte to obtain a composite positive electrode powder; The sulfide solid electrolyte is first pressed to obtain a sulfide layer; Placing a first halide solid electrolyte on one side of the sulfide layer for a second pressing to obtain a sulfide layer + a halide layer; Placing the composite positive electrode powder on the side of the sulfide layer + halide layer where the halide layer does not contact the sulfide layer for a third pressing to obtain a sulfide layer + halide layer + positive electrode layer; The lithium-indium alloy is placed on the side of the sulfide layer + halide layer + positive electrode layer where the sulfide layer does not contact the halide layer, and a fourth pressing is performed to form a structure of a negative electrode layer + sulfide layer + halide layer + positive electrode layer to obtain the high temperature resistant all-solid-state lithium battery.
10. Use of the high temperature resistant all-solid-state lithium battery according to any one of claims 1 to 8 or the high temperature resistant all-solid-state lithium battery prepared by the preparation method according to claim 9 in a high temperature environment.
Citation Information
Patent Citations
Composite positive electrode, solid-state lithium ion secondary battery, and electric device
CN115172653A
All-solid-state lithium battery and preparation method thereof
CN115207456A
All-solid-state lithium ion battery
CN117154202A
battery
US20220336850A1
Cited By
Double-layer solid electrolyte membrane, preparation method thereof and all-solid-state battery
CN119627200A
